2022
DOI: 10.1155/2022/7181075
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Plasma Arc Cutting Parameters on Machining of Inconel 718 Superalloy

Abstract: Nickel-based super composites are widely applied in the industry. These alloys withstand high thermal debility conditions and give better strength to machine parts in aviation, biomechanical, marine, and vehicle commerce. Nickel-based alloys have high quality, corrosion resistance, and high heat refusal. Inconel 718 is one such composite extensively utilized in these loading circumstances because of chemical stability, mechanical friction, high thermal corrosion, and high stability. During the cutting procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…HPMs are essential for the manufacturing industry, particularly for high-stress applications, where standard metals are not suitable. HPMs such as titanium alloys, nickel alloys, and aluminum alloys have been widely used in critical engine and structural transport applications for their excellent properties, including high strength-to-weight ratio, corrosion resistance, and thermal stability [9][10][11]. However, the conventional manufacturing (CM) of these metals involves lengthy, expensive, and complicated processes [8,[12][13][14] which may limit their adoption.…”
Section: Introductionmentioning
confidence: 99%
“…HPMs are essential for the manufacturing industry, particularly for high-stress applications, where standard metals are not suitable. HPMs such as titanium alloys, nickel alloys, and aluminum alloys have been widely used in critical engine and structural transport applications for their excellent properties, including high strength-to-weight ratio, corrosion resistance, and thermal stability [9][10][11]. However, the conventional manufacturing (CM) of these metals involves lengthy, expensive, and complicated processes [8,[12][13][14] which may limit their adoption.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [12] investigated the effect of a blunt round edge tool radius and microtexture characteristics on milling cutting forces and observed that the radius of a blunt round edge has the greatest effect, trailed by the tool diameter, cutting edge distance, spacing, and depth. A cutting force estimation framework centred on FEM and nonrational basis splines (NURBS) for a single blade is suggested [13], in which the cutting force estimation technique is more productive than the FEM and NURBS methods because it is established by simulation data, which may not necessitate the use of cutting force information from experiments. Fairly forecasting force is critical for improving machining performance and life of the tool [14], and all coefficients of force frequently vary with the angle of rotation in milling, and a good prediction is possible with FEM as it agrees with the experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its excellent stability and strength at a high temperature of around 700 °C, Inconel 718 was deployed [12]. Inconel 718 has been used to manufacture hot sections in the aerospace components such as turbines and engines [13]. During machining, Inconel 718 alloy has poor thermal conductivity and high chemical affinity, which results in hard machining or cutting the material [14].…”
Section: Introductionmentioning
confidence: 99%